BRSMG Caçula: very early upland rice cultivar for Minas Gerais - Antônio Alves Soares (Crop Breeding and Applied Biotechnology, 2013)
The basic objective of the upland rice breeding program developed in the state of Minas Gerais is to make new commercialcultivars available. A new cultivar named BRSMG Caçula is being released, with the main traits: earliness, lodging tolerance, grainquality, disease tolerance, and high grain yield.